DEVELOPMENT AND COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF A NEW EXPERIMENTAL MODEL OF ABDOMINAL SEPSIS - Khamdamov, B.Z.; Khotamov, I.E.; Khakimboeva, K.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Background. The main goal of modelling pathological processes is to solve the problem of an entire link of translational medicine, which is aimed at developing treatment methods and introducing them into clinical settings. Material and methods. The work is experimental and was carried out on 40 beads of both sexes of the Wistar line. Various variants of abdominal sepsis were simulated in animals, including the original technique developed by us. Results. Comparative characteristics of the reproducibility of various variants of experimental models of abdominal sepsis showed high values of positive results among animals of the C-series. The reproducibility rate of abdominal sepsis was 28.5% higher than among Series-A and Series-B animals. At the same time, lethality among the animals of the C-series was minimal. Conclusion. The proposed version of the model of abdominal sepsis makes it possible to achieve the formation of several pathogenetic mechanisms that have a reasonable place in clinical practice.